Relationship Between Patients’ Knowledge of Beyond-Use Dates for Nonsterile Compounded Medications and Their Storage Behavior at Sewon 1 Primary Health Center: Relationship Between Patients’ Knowledge of Beyond-Use Dates for Nonsterile Compounded Medications and Their Storage Behavior at Sewon 1 Primary Health Center - Ari Susiana Wulandari; Abd. Sukri S. Manusu; Baiq Husnul Hotimah Septiandi; Raviqoh Annur Jannah; Sri Suprapti; Eva Nurinda; Diki Aprianto A; Despita Pramesti (LPPM Universitas Abdurrab, 2025)
The principal issue frequently encountered in society is confusion regarding drug stability, especially beyond use date. Many people are unfamiliar with beyond use date and expiration date. This condition often leads to improper medication storage. The aim of this study was to analyze the relationship between a patient's knowledge about beyond use date and their behavior in storing and using medication. A cross-sectional study was conducted on 80 respondents at Sewon 1 Primary Health Center, Yogyakarta, from January to February 2025. Using a validated questionnaire and purposive sampling, data was analyzed with the chi-square test. The results of the univariate analysis showed that patients' knowledge about beyond use date was mostly in the high category, which included 42 respondents (52.5%). Accordingly, patients's medication storage behavior was also mostly classified as good, accounting for 48 respondents (60.0%). Based on descriptive statistics, the mean value for the knowledge was 21.0 ± 1.701, while the mean value for the behavior variable was 41.38 ± 3.605. The conclusion of this study showed that there was a significant relationship between patients' knowledge about beyond use date of non-sterile compounded drugs and their medication storage behavior, with a significance value of 0.015 (p<0.05).